Dual Regulation of Phosphatidylserine Decarboxylase Expression by Envelope Stress Responses - Hassoun, Yasmine; Bartoli, Julia; Wahl, Astrid; Viala, Julie Pamela; Bouveret, Emmanuelle (Frontiers in Molecular Biosciences, 2021)
Bacteria adapt to versatile environments by modulating gene expression through a set of stress response regulators, alternative Sigma factors, or two-component systems. Among the central processes that must be finely tuned is membrane homeostasis, including synthesis of phospholipids (PL). However, few genetic regulations of this process have been reported. We have previously shown that the gene coding the first step of PL synthesis is regulated by σE and ppGpp, and that the BasRS (PmrAB) two component system controls the expression of the DgkA PL recycling enzyme. The gene coding for phosphatidylserine decarboxylase, the last step in phosphatidylethanolamine synthesis is another gene in the PL synthesis pathway susceptible of stress response regulation. Indeed, psd appears in transcriptome studies of the σE envelope stress Sigma factor and of the CpxAR two component system. Interestingly, this gene is presumably in operon with mscM coding for a miniconductance mechanosensitive channel. In this study, we dissected the promoter region of the psd-mscM operon and studied its regulation by σE and CpxR. By artificial activation of σE and CpxRA stress response pathways, using GFP transcriptional fusion and western-blot analysis of Psd and MscM enzyme production, we showed that the operon is under the control of two distinct promoters. One is activated by σE, the second is activated by CpxRA and also responsible for basal expression of the operon. The fact that the phosphatidylethanolamine synthesis pathway is controlled by envelope stress responses at both its first and last steps might be important for adaptation of the membrane to envelope perturbations.